Designing Student Apartments With Green Building Concept on Ismail Harun Street - Dwira Nirfalini Aulia; Nida Andini Putri Tanjung (Talenta Publisher, 2020)
Apartments with green building concept are vertical dwellings that are built using the basic rules of green building namely energy efficiency and renewable energy, efficient use of air, use of environmentally friendly materials, use of waste and materials, improvement of good indoor air circulation, and sustainable development and smart growth. This concept is used as a fulfillment of housing needs for students around Universitas Negeri Medan, which is environmentally friendly. The concept of green building is expected to reduce household pollution generated from student apartments, which can reduce the quality of the surrounding environment and also reduce the costs of maintenance and operation of the apartment, which can have an impact on the quality of resident’s life. In the process of designing this apartment, the writer uses a quantitative-correlative approach to find what is needed by the apartment user. The process of designing an apartment with this concept will produce an environmentally friendly building that can save water use up to 53.28%. This student apartment is equipped with a solar power plant that can save PLN electricity use by up to 33%. Each apartment unit and room in the management office is also designed with natural light and natural air circulation in mind to reduce the use of electricity and air conditioning. This apartment also utilizes human waste by processing it into biogas using dome reactors.